The Effectiveness of Critical Thinking Skill Training on Iranian EFL Learners' Reading Comprehension and Reading Strategy Use - V.S. Vahedi; M. Ebrahimi (Fanāvarī-i āmūzish, 2017)
The current study aimed to investigate the effect of critical thinking skill training on Iranian EFL learners' reading comprehension and reading strategy use. To this aim, 140 highly homogenous students were chosen and two groups shaped; one group was provided with critical thinking skill training, whereas the control group did not receive any training regarding critical thinking skills.  Before and after the tutorial, a reading comprehension test and a reading strategy questionnaire were administered. The data were analyzed using ANCOVA.  The results indicated that the experimental group outperformed their counterparts in the control group in the reading achievement posttest (p<0.05). Furthermore, subjects in the experimental group used metacognitive, social and compensatory strategies more frequently after the treatment as compared to their usage of the same strategy types before starting out the tutorial. In sum, the current study revealed that critical thinking strategy training played an important role in enhancing learners' reading comprehension ability and also their reading strategy use. In other words, the introduction of elements of the constructivist pedagogy accompanied with specific strategies aimed at encouraging higher level thinking can lead to higher learning outcomes in the process of learning a second/forein language.